Quantificação e caracterização da biomassa florestal em plantios de curta rotação - Eloy, Elder (2013)
This study aimed to quantify and characterize forest biomass by determining the biomass production, the power calorific value, of basic density and energy productivity of species: Acacia mearnsii De Wild, Eucalyptus grandis W. Hill ex Maiden, Mimosa scabrella Benth and Ateleia glazioviana Baill, distributed in different planting space: 2.0x1.0 m; 2.0x1.5 m; 3.0x1.0 m and 3.0x1.5 m, the first and third year after planting. Therefore, it was considered an experiment located in the city of Frederico Westphalen-RS, installed in a randomized complete block design with three replications in a split-plot. After the felling of the trees were removed disks of 2.0 cm thick at positions Tree: 0% (base), 1.30 m (diameter at breast height - DBH), 25%, 50%, 75% and 100% of the total height, for evaluations of wood biomass and bark, power calorific value and higher basic density. To determine the biomass and power calorific value upper branches and leaves, stratified samples were taken and determined its final weight. The determination of power calorific value of the trees was carried out from the weighting of the values obtained in each compartment (wood, bark, twig and leaf). The determination of basic density weighted was performed from the weight of the total shelled with values recorded discs collected at different positions along the stem. Since the energy productivity of biomass was determined from the values of aboveground biomass and power calorific value of each compartment. The results showed that different planting spacing produced different amounts of aboveground biomass and hence the energy productivity of four tree species studied in the first and third year after planting. Minors planting spacing led to an increase in biomass production per unit area in different species, and we found a systematic tendency negative to living space provided, mainly influenced by the number of trees in the different spacing. Thus, species that have excelled in the production of biomass were Eucalyptus grandis and Acacia mearnsii. The basic density weighted of the wood did not show a variation of increase or decrease over time, and the species Acacia mearnsii and Ateleia glazioviana showed the highest values of this property. However, the different levels spacing did not induce the systematic variation of power calorific value and higher basic density in the studied species. The energy yields obtained in the third year, for all species are higher than those of the first year. The species Eucalyptus grandis has the greatest potential for energy productivity, followed by Acacia mearnsii, Mimosa scabrella, Ateleia glazioviana. It is recommended to use the lowest row spacing (2.0 x 1.0 m) for all studied forest species in short rotation plantations with greater production of biomass for energy purposes.